Kualitas Pelayanan Badan Penyelenggaraan Jaminan Sosial (BPJS) Dari Mandiri Ke Penerima Bantuan Iuran (PBI) Di Sistem Layanan Dan Rujukan Terpadu (SIRT) Graha Pancakarsa Dinas Sosial Kabupaten Bogor - Daffa Fawaz Musafa; Muhammad Khoirul Anwar (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
This research was motivated by the discovery of a lack of quality of the integrated service and referral system which had not been maximized in the submission of independent social security administration bodies to recipients of contribution assistance to the community, which caused the community to be hampered in the administrative process of applying for independent social security administration bodies to recipients of contribution assistance. Therefore, this research aims to determine the quality of service in the integrated service and referral system to the community. This research uses descriptive qualitative methods with data collection methods through observation by observing the integrated service and referral system to the community. The data collection technique uses interviews with the head sub-divisions and five communities. The results of this research show that the quality of service of the independent social security administration agency to recipients of social assistance at Slrt Graha Pancakarsa Bogor Regency social service, the community assesses with 5 dimensions: Tangible (tangible), Reliability (reliability), Responsiveness (responsiveness), Assurance (guarantee), Empathy (empathy). Thus, the quality of service at Slrt Graha Pancakarsa helps the community.